The Impact of Workplace Bias on African American Women in the United States Financial Institutions - McAllister, Jawondolyn Bettricia (Digital Repository of Theses - SSBM Geneva, 2025)
This study examines the underrepresentation of African American women in leadership roles within the United States financial services industry. Also, it demonstrates how these patterns are shaped by institutional, cultural, and structural factors. Specifically, drawing on historical and contemporary literature, policy reviews, and qualitative survey responses, the research investigates barriers such as racial bias, limited access to mentorship, and with restricted opportunities for high-level positions. Moreover, the findings in fact indicate that racial hierarchies continue to persist within organizational structures, and these hierarchies, when combined with limited progress in implementing substantive diversity, equity, and inclusion policies, continue to present barriers to advancement. Additionally, the findings indicate that racial hierarchies continue to persist within organizational structures, and these hierarchies, when combined with limited progress in implementing substantive diversity, equity, and inclusion policies, continue to present barriers to advancement. Furthermore, although affirmative action policies have been in place for several decades, representation in executive and Csuite roles still remains disproportionately low. In addition, Environmental, Social, and Governance (ESG) frameworks are identified as potential mechanisms that could be used to enhance transparency, fairness, and inclusiveness. The results suggest that exclusionary systems persist even when organizations have adopted formal diversity policies, and therefore the study recommends measurable institutional reforms, the integration of equity metrics into leadership evaluations, and sustained accountability measures to expand leadership opportunities for African American women in finance.